An ethical foundation for global citizenship education: a neo-Confucian perspective - Tan, Charlene (Journal of beliefs and values, 2020)
Offering an ethical foundation for global citizenship education, this paper draws upon the ideas of neo-Confucian thinker Wang Yangming. Focussing on UNESCO’s goal to help learners acquire a sense of belonging to a broader community and humanity, this paper elucidates Wang’s concept of innate knowledge (liangzhi). The article explains how Wang posits a shared humanity that is premised on moral knowledge inherent in all human beings. He further argues for the extension of innate knowledge by eliminating our selfish tendencies and manifestations that alienate us from other people. Two major implications for global citizenship arising from Wang’s ideas are highlighted. First, Wang’s notion of innate knowledge, by affirming human dignity, equality and potential, underpins and constitutes the vision of shared humanity in global citizenship. Secondly, Wang’s recommended pedagogical approaches promote global citizenship by foregrounding the moral cultivation of learners.